ORGANIC FERTILIZATIONTO INCREASE YIELD OF SOYBEAN VAR. ANJASMORO INTERCROPPED WITH VARIOUS VARIETIES OF RED RICE UNDER AEROBIC IRRIGATION SYSTEM - Hapisah, Hapisah; Wangiyana, Wayan (Jurnal Silva Samalas, 2020)
This study aimed to examine the effect of organic fertilization and red rice varieties on growth and yield of soybean grown together with various red rice varieties under aerobic system irrigation. The pot experiment, carried out in the plastic house of the Faculty of Agriculture, University of Mataram in the Narmada experimental farm, was arranged according to the Completely Randomized Design, with three replications and two treatment factors, namely organic fertilization using bokashi of cattle manure (16 ton/ha) applied at rice planting (P0 = without; P1 = with organic fertilizer), and red rice varieties (V1= AM-G2, V2= AM-G4, V3= AM-G9, V4= AM-G10, V5= Inpari 24, V6= Inpago Unram-1), under aerobic irrigation system through sub-irrigation. Pre-germinated soybean seeds (â€œAnjasmoroâ€ variety) were relay-planted 18 days after planting rice. The results indicated that organic fertilization only significantly increased weights of dry stover, dry pods and grain yield of soybean, whereas rice varieties only affected dry pod weight, and the interaction effect was significant only on soybean grain yield, with the highest average of 17.77 g/pot (equivalent to 2.84 ton/ha) in soybean relay-planted with organic-fertilized rice of â€œInpari 24â€ variety, which grain yield was the lowest (11.1 g/pot or 1,78 ton/ha), indicating that there were below-ground competitions between rice and soybean grown in one pot. However, in the treatment producing the highest rice grain yield (40.9 g/pot or 6.54 ton/ha), the average soybean grain yield was 13.7 g/pot (or 2.19 ton/ha), which is still quite high (far above the national productivity), so relay-planting soybean with rice crop in aerobic irrigation systems supplied with organic fertilizer is still feasible.